Implementasi Pendidikan Agama Islam melalui Hafalan Hadits Beserta Artinya di TKIT Miftahul Jannah Salatiga - Junedi, Junedi; Afifah, Nur; Nursikin, Mukh (Lembaga Yasin AlSys, 2022)
The objectives of this research are to describe the level of need for early childhood character development through rote learning and its meaning at TKIT Miftahul Jannah Salatiga Types of Research- This research is research and development. Research Subjects - Research subjects are students and educators ( teacher) The analysis technique - the data used is to analyze the data in a descriptive and practical way. The results of the study - indicate the existence of (i) the level of need for developing Islamic character in Early Childhood through rote learning activities along with their meanings at TKIT Miftahul Jannah, there are students who have not interested in participating in memorization learning activities and their meanings. (ii) an overview of the design of Islamic character development of students through memorizing hadith and their meanings in the form of guides and interesting learning models. (iii) The level of content validity and practicality of Islamic character development through Lui rote learning has it and it means that there is a significant influence on the results of the evaluation of the Islamic character of Early Childhood, namely 98% of the students who are the subject of the trial giving a positive response to the development of the character of Early Childhood through rote learning activities and their meanings.